Blogueiras negras: luta por reconhecimento social e feminismo negro na internet - Macedo, Poliana Ribeiro Arcelino de (2018)
This dissertation intends to analyze the discursive production of Brazilian black women based on the Blogueiras Negras webpage. Initially reflections on the trajectory of Brazil’s black women movement and the development of a black feminist way of thinking are introduced. It is the aim of this work to comprehend the meaning of reports and publications from Blogueiras Negras, which are explored from three different angles: the autobiographical report, the process of discovering one’s blackness and the denunciation of marginalization and violence against black people. We support our methodology on virtual ethnography to map media and platforms that provide content created by and for black women on the internet. At first, the analytical keys to think about such content dwell within the concepts of experience and reflexivity, both highly regarded concepts to black feminism. We also strive to reflect on the moral orientation of the group from the Blogueiras Negras blog regarding the currentduality existing between the normative paradigms of acknowledgement versus redistribution. We intend to investigate the relevance of the aforementioned paradigms as the foundation for those women’s actions. Whatever emerges from this matter is part of a black diasporic counterculture that contests the non-realization of illuminist justice ideals.